Os verdadeiros filósofos enquanto 'bacchoi': a transposição platônica dos mistérios órficos no 'Fédon' - Braz, Giovanna (Universidade Federal de São Carlos, 2020)
In the Phaedo Plato presents his notion of philosophy through an appropriation of the orphic mysteries: through an elaborate mimetic work, the philosopher adapts to his thought elements of both sacred discourses (hieroi logoi) and orphic initiations (teletai), approaching the practice of philosophy closer to the initiatic experiences. The aim of this research is to understand precisely this approach between philosophy and the mysteries that occurs in the Phaedo. Taking the notion of “transposition” as an instrument of criticism and analysis of Plato's uses of orphic doctrines, we see how the philosopher transposes various elements from the mystical realm to his own philosophy, from the central concern with death to the doctrines about the soul and its salvation after death. Such transposition culminates in the identification between the true philosophers (alethos philosophoi) and the orphic bacchoi (69c-d).
The true philosophers as 'bacchoi': the platonic transposition of the orphic mysteries in the 'Phaedo'
Keywords: Platão; Fédon; Verdadeiros filósofos; Transposição; Mistérios órficos; Plato; Phaedo; True philosophers; Bacchoi; Transposition; Orphic mysteries; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA